2010
DOI: 10.1007/s00432-010-0764-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of related factors associated with radiation pneumonitis in patients with locally advanced non-small-cell lung cancer treated with three-dimensional conformal radiotherapy

Abstract: The comprehensive values of DVH parameters, chemotherapy, and gender have independent effects on the occurrence of RP. Most of DVH parameters were associated with the occurrence of RP. The curve shape composed of multiple points in DVH parameters was more important than any single DVH parameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 24 publications
2
15
2
Order By: Relevance
“…It is worth mentioning that this study has confirmed previous reports that MLD is a significant predictor for RP, regardless of the calculation method (6, 13, 14), although some lung DVH studies neglected to mention the method of DVH computation (11, 1518). In the studies that clearly specified lung volume definition, more researchers used the BL-GTV method recently; however, methods vary from study to study (5, 6, 19, 20).…”
Section: Discussionsupporting
confidence: 87%
“…It is worth mentioning that this study has confirmed previous reports that MLD is a significant predictor for RP, regardless of the calculation method (6, 13, 14), although some lung DVH studies neglected to mention the method of DVH computation (11, 1518). In the studies that clearly specified lung volume definition, more researchers used the BL-GTV method recently; however, methods vary from study to study (5, 6, 19, 20).…”
Section: Discussionsupporting
confidence: 87%
“…Combination of chemotherapy and RT has been well reported increasing the risk of pulmonary injury, either sequential [16] or concurrent [12,13]. Weekly docetaxel with concurrent conventional radiotherapy resulted in 47% grade ≥3 RP [13]; Carboplatin plus taxanes with concurrent 3D-CRT resulted in 32% grade ≥3 RP [12].…”
Section: Discussionmentioning
confidence: 99%
“…Combination of chemotherapy and RT has been well reported increasing the risk of pulmonary injury, either sequential [8] or concurrent [9]. The targets of drugs with direct toxicity to human cells were consistent with the radioactive rays.…”
Section: Discussionmentioning
confidence: 90%